2007
DOI: 10.1182/blood-2006-12-061309
|View full text |Cite
|
Sign up to set email alerts
|

An NKT-mediated autologous vaccine generates CD4 T-cell–dependent potent antilymphoma immunity

Abstract: Relapses occurring in most patients with lymphoma after antibody or chemotherapy highlight a need for effective vaccination approaches. Autologous tumors are ideal sources of patient-specific tumor antigens for vaccines; however, their poor immunogenicity has been a major obstacle in practice. Natural killer T (NKT) cells have recently emerged as crucial regulators of autoimmunity and tumor immunosurveillance. Here, we show that an autologous lymphoma vaccine that activates NKT cells generated tumorspecific pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 35 publications
5
67
0
1
Order By: Relevance
“…Because this chemotherapeutic agent is in routine clinical use for leukemia induction and consolidation, 67,68 these results are of particular relevance clinically. 27,29 Our results support a previous in vivo study with C1498 in which mice treated with a granulocyte macrophage colony-stimulating factor-secreting irradiated cell vaccine 5 or 7 days after cytarabine treatment were protected against the development of leukemia, despite transient development of severe neutropenia and lymphopenia following chemotherapy. 59 We have demonstrated successful combination of immunotherapy after chemotherapy pretreatment of leukemic mice and have shown that cytarabine alone did not induce changes to the immune environment that could be detected by day 20.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Because this chemotherapeutic agent is in routine clinical use for leukemia induction and consolidation, 67,68 these results are of particular relevance clinically. 27,29 Our results support a previous in vivo study with C1498 in which mice treated with a granulocyte macrophage colony-stimulating factor-secreting irradiated cell vaccine 5 or 7 days after cytarabine treatment were protected against the development of leukemia, despite transient development of severe neutropenia and lymphopenia following chemotherapy. 59 We have demonstrated successful combination of immunotherapy after chemotherapy pretreatment of leukemic mice and have shown that cytarabine alone did not induce changes to the immune environment that could be detected by day 20.…”
Section: Discussionsupporting
confidence: 80%
“…Interactions between DCs and NKT cells promote CD40 signaling, leading to DC activation, which increases the capacity of DCs to stimulate peptide-specific T cells. 23,24 Significantly, vaccines comprising irradiated tumor cells pulsed with a-GalCer have been shown to be effective in murine models of hematopoietic malignancies, including acute myeloid leukemia (AML) and acute lymphoid leukemia, 23,27,28 and in other malignancies. 25,27,29 Cancer-associated immunosuppression can present a significant barrier to effective vaccine-based immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…␣GalCer, the ligand of type I NKT cells, has been widely used as an adjuvant to enhance antitumor immunity, not only as a free form (34) but also as a loaded form onto various CD1d-expressing cells, including DCs (19,20), B cells (21,22), or tumor cells (35)(36)(37). Paradoxically, however, NKT cells have also been reported to suppress tumor immunosurveillance (38,39) rather than induce protective immunity (40,41) in several tumor models.…”
Section: Discussionmentioning
confidence: 99%
“…NKT cells are appreciated for their ability to regulate autoimmunity and tumor surveillance and a role for selectively activating NKT in vivo is beginning to be explored. 67,68 Adoptive cellular immunotherapy for melanoma While melanoma is generally not a pediatric malignancy, the infusions of tumor-specific T cells has resulted in seven important principles that can be generalized for the field of adoptive immunotherapy for pediatric tumors. (i) The first observation is that autologous tumor-specific T cells can be identified in patients with cancer.…”
Section: Adoptive Cellular Immunotherapy Using Allodepleted T Cellsmentioning
confidence: 99%